INSTITUSIONALISASI LEMBAGA DISTRIBUSI PANGAN MASYARAKAT (LDPM) - Koswara, Asep (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2017)
Food security is a trending topic and is a global problem that is interesting to continue to be discussed. The problem of food security cannot be separated from the three (3) main aspects, namely the aspect of production, distribution and consumption. One of the empowerment program of food security that is being done is the strengthening of the Public Food Distribution Institution Program or commonly abbreviated LDPM. The program provides grant assistance in the form of social capital (social assistance) to the combined group of farmer beneficiaries remedy used as venture capital to business units owned. The success of the program needs to be institutionalized norms or rules that exist in the program LDPM the combined members of farmer groups in order to target the norms or rules become part of the lifestyle people of Malang district. This study aims to determine how the institutionalization LDPM members of farmer groups at the transmitter and how farmers understand. The study was conducted using qualitative descriptive approach and conducting depth inter views and observations to the informants as many as 30 people. Based on their search conducted is known that the members of the Joint LDPM transmitter farmer groups have not been fully institutionalized because the norms that emphasized not fully accepted by members of the community because in line with the local wisdom that is in the region.